2023
DOI: 10.1002/cpt.2978
|View full text |Cite
|
Sign up to set email alerts
|

Response to the FDA Decision Regarding DPYD Testing Prior to Fluoropyrimidine Chemotherapy

Abstract: Fluoropyrimidine (FP) chemotherapy is associated with severe, life‐threatening toxicities, particularly among patients who carry deleterious germline variants in the DPYD gene. Pretreatment DPYD testing is standard of care throughout most of Europe; however, it has not been recommended in clinical practice guidelines in the United States. Due to increased risk of severe toxicity, a Citizen's Petition asked the US Food and Drug Administration (FDA) to update language in FP drug labels to recommend DPYD testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Given the severity of toxicity, pre‐emptive testing is a powerful tool to identify DPD deficiency before treatment initiation 8 , 23 and, thus, future considerations should include universal recommendations for DPD deficiency testing. 3 , 24 , 25 Additionally, current guidelines need to be updated to reflect that c.1236G>A may not be a reliable variant to detect decreased DPD activity. Tests predicting DPD activity using only c.1236G>A should contain explicitly clear language stating that this tagSNP is not in complete LD with the underlying causal variant, which in rare cases may lead to a false‐positive prediction of decreased DPD activity, which may trigger an inappropriate dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Given the severity of toxicity, pre‐emptive testing is a powerful tool to identify DPD deficiency before treatment initiation 8 , 23 and, thus, future considerations should include universal recommendations for DPD deficiency testing. 3 , 24 , 25 Additionally, current guidelines need to be updated to reflect that c.1236G>A may not be a reliable variant to detect decreased DPD activity. Tests predicting DPD activity using only c.1236G>A should contain explicitly clear language stating that this tagSNP is not in complete LD with the underlying causal variant, which in rare cases may lead to a false‐positive prediction of decreased DPD activity, which may trigger an inappropriate dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Other bene ts of outsourcing to a commercial lab include less upfront cost and time to launch testing [38]. On the other hand, in-house testing has bene ts including greater control over interpretation (e.g., using activity score or metabolic phenotype), EMR integration (e.g., ordering and results return), and inclusion of alleles of interest, such as DPYD variants carried by non-Europeans [39] to increase testing equity [24,[39][40][41]. At the time of our survey all sites were currently using genotyping and one site was in the planning stages of using DPYD sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in Europe found that the number of DPYD genotyping tests doubled from 2019 to 2021 [17], primarily due to the European Medicine Agency (EMA) recommendation for pre-treatment DPD testing in 2020 [18] and consistent testing reimbursement [17]. Pharmacogenetic (PGx) testing to optimize treatment is rapidly expanding within the US [19,20] across a number of therapeutic areas and drugs [21,22]; however, DPYD testing prior to FP treatment is not currently recommended by any US-based clinical oncology guidelines or the FDA [23][24][25]. According to a 2017 survey, only 20% of US medical oncologists had ever ordered pre-treatment DPYD testing, despite 98% agreeing that patients with DPD de ciency have increased FP toxicity risk [26].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme represents the rate-limiting step responsible for the rapid breakdown of the chemotherapeutic drug 5-FU. Deficiency in dihydropyrimidine dehydrogenase activity can lead to severe and potentially fatal toxicity, with nearly 30% of patients with reduced activity experiencing severe toxicity during chemotherapy [ 9 , 11 , 23 ]. The co-crystal structure of dihydropyrimidine dehydrogenase from pig liver ( Sus scrofa ) has been resolved at a 1.9 Å resolution (PDB ID 1H7X) [ 24 ].…”
Section: The Binding Mode Of 5-fumentioning
confidence: 99%
“…In the catabolic pathway, 5-FU is converted into dihydrofluorouracil by dihydropyrimidine dehydrogenase, with most of it being degraded in the liver [ 11 , 12 ]. This leads to the formation of α-fluoro-β-alanine and α-fluoro-β-ureido propionic acid, which are excreted through the kidneys.…”
Section: Introductionmentioning
confidence: 99%